DETERMINANT OF SAFETY AND WORKPLACE SAFETY IN WORK ENVIRONMENT PT. PERUSAHAAN LISTRIK NEGARA (PERSERO) SULUTTENGGO AREA - Lumintang, Genita Gracia; Kindangen, Paulus; -, Adolfina (Archives of Business Research, 2021)
The purpose of this research is to examine the impact of organizational characteristics, and individual characteristics on physical environment component, psychosocial component, and behavior component toward workplace safety and health in PT. PLN (Persero) Suluttenggo area. The object of this research is permanent employees or outsourcing employees in PT. PLN (Persero) Suluttenggo Area. Research Design used in this research is survey research, in which the sample collected by distributing questionnaires to 50 permanent employees and outsourcing employees that already worked as work partner of PT. PLN (Persero) Suluttenggo Area. As for the analysis instrument is using partial least squares (PLS). The result shows that organizational characteristic has a positive influence on the components of work environment, either physically or psychosocially; and on behavior as well as the workplace health and safety. On the other hand, individual characteristic doesn’t have an influence. The result of this research also shows that only the individual behavior that has a positive influence on workplace health and safety, while physical work environment does not, meanwhile psychosocial component has a negative influence on workplace health and safety.